Quorum Quenching of P. aeruginosa by Portulaca oleracea Methanolic Extract and Its Phytochemical Profile - Hala I. Al-Daghistani; Sina M. Matalqah; Khalid A. Shadid; Lubna F. Abu-Niaaj; Sima Zein; Raeda M. Abo-Ali (Pathogens)
Quorum sensing (QS) is a molecular communication mechanism among bacterial cells. It is critical in regulating virulence factors, motility, antibiotic resistance, and biofilm formation. Pseudomonas aeruginosa is a Gram-negative opportunistic pathogen linked to healthcare-associated infections, food poisoning, and biofilm formation. Treating infections caused by pathogenic bacteria has become a challenge due to the development of multi-antibiotic resistance upon continuous exposure of bacteria to antibiotics. An alternative strategy to conventional antimicrobials to decrease the bacterial pathogenicity is QS inhibition, also known as quorum quenching. Using plant-derived compounds is an environmentally friendly strategy to block the bacterial QS and inhibit bacterial growth. Portulaca oleracea is a popular plant in different countries and is also used in traditional medicine. It is widely consumed raw in salads and as garnishes, though it can be cooked as a vegetarian dish. This study evaluates the antimicrobial activity of the methanolic extract of P. oleracea and its effectiveness in blocking or attenuating the QS of P. aeruginosa. The agar well diffusion method used for screening the antibacterial activity showed a significant growth inhibition of P. aeruginosa by the extract at 500 mg/mL with a minimum inhibitory concentration of 31.25 mg/mL. A bioindicator bacterium, Chromobacterium violaceum CV026, was used to determine the effect of the methanolic extract on the QS of P. aeruginosa. The results indicated a significant reduction in biofilm formation, pyocyanin production, and LasA staphylolytic activity. The phytochemical analysis by Gas Chromatography–Mass Spectrometry showed that the methanolic extract contained several phenols, alkaloids, esters, and other compounds previously reported to have antibacterial and antioxidant effects. These findings highlight the effectiveness of P. oleracea methanolic extract in attenuating the QS and virulence factors of P. aeruginosa. This study suggests that P. oleracea is an important source of natural antimicrobials and its use would be beneficial in food and pharmaceutical applications.